Polyurethane, epoxy resin and polydimethylsiloxane altered biofilm formation and mussel settlement. (March 2019) - Liang, Xiao; Peng, Li-Hua; Zhang, Shuo; Zhou, Shuxue; Yoshida, Asami; Osatomi, Kiyoshi; Bellou, Nikoleta; Guo, Xing-Pan; Dobretsov, Sergey; Yang, Jin-Long
Abstract: In many environments, biofilms are a major mode and an emergent form of microbial life. Biofilms play crucial roles in biogeochemical cycling and invertebrate recruitment in marine environments. However, relatively little is known about how marine biofilms form on different substrata and about how these biofilms impact invertebrate recruitment. Here, we performed a comparative analysis of a 28-day-old biofilm community on non-coated (a control glass) and coated substrata (polyurethane (PU), epoxy resin (EP) and polydimethylsiloxane (PDMS)) and examined the settlement of Mytilus coruscus plantigrades on these biofilms. PU, EP and PDMS deterred the development of marine biofilms by reducing the biofilm biomass including the biofilm dry weight, cell density of the bacteria and diatoms and chlorophyll a concentrations. Further analysis of bacterial community revealed that EP altered the bacterial community composition compared with that on the glass substrata by reducing the relative abundance of Ruegeria (Alphaproteobacteria) and by increasing the relative abundance of Methylotenera (Betaproteobacteria) and Cyanobacteria in the biofilms. However, bacterial communities developed on PU and PDMS, as well as glass and PU, EP and PDMS did not exhibit differences from each other. The M. coruscus settlement rates on biofilms on PU, EP and PDMS were reduced by 20–41% compared with those on the glass after 28 days. Thus, the tested coatings impacted the development of marine biofilms by altering the biofilm biomass and/or the bacterial community composition. The mussel settlements decreased in the biofilms that formed on the coatings compared with those on non-coated glass. Highlights: PU, EP and PDMS deterred biofilm development by reducing biofilm biomass. Coatings impact the biofilm formation by altering bacterial community composition. Mussel settlement on biofilms developed on coatings decreased from 20% to 41%.